O adolescente pelo adolescente : a dialogicidade das narrativas de si articuladas à lógica de consumo e às mídias sociais - Ew, Raquel de Andrade Souza (2015)
This study has as central theme the investigation on how self narratives are built among teenagers. The goal is to understand and to analyze how teens build narratives about themselves linked with consumption practices, by analyzing the different positions of the self, and the use of social media. In this context, this research analyzes the factors that traverse and which become important tools in configuring the self narratives in teenagers. We deal with three important social discourse articulators which favor the assumption, relationship, and creation of the self narratives, namely: consumption, narratives dialogicity, and social media access. Therefore, we divided this research into three empirical studies, which constitute the body of this paper. The first study focuses on the self narratives development following the logic of consumption. In this study, there is a reflection about the construction of the self narratives from the composition and access to cultural elements valued as aspects to be developed and acquired. The second study addresses how these self narratives constitute a dynamic and dialogical way to create dialogues between I Others, gaining hierarchy space and values, from contradiction, movement, and context. Finally, in the third study, we perceive how teenagers use social media, through Facebook, in the process of building of the self in virtual space. Analysis is based on a material extract, gathered by accessing the self narratives in virtual context, examining dialogicity and issues related to tension between author and audience. The studies have a qualitative nature, and their data collection was carried out using interviews with a perspective of approaching the teenagers, through virtual ethnography, for the study on Facebook